الأفعال الاجتماعية في حكاية خرافية "السلطان المسحور" لمحمد عطية الإبراشي من خلال ماكس فبير - عين البريرة; أحمد خليل; محمد هاشم (Prosiding Konferensi Nasional Bahasa Arab, 2017)
Abstract: Of literature is a fairy tale and it is kind of folk stories. In this topic of research is the fairy tale of "as-Sultan al-Mashur". There is a lot of dialogue and monologue involving social acts. Social acts are a sociological study whose study concerns people as a social creature, and actions are the consequences of social impact. Max Weber is the founder of modern social Science from Germany, which focuses on social actions and must aim for a particular purpose and share with the other. Feber is divided into his four-species theory: The traditional act, the emotional act, the moral value act, and the moral rationality act. And the questions are what the word social verbs in the fairy tale of " as-Sultan al-Mashur" of Muhammad Atiyyatul Ibrasyi in Max Weber's theory, and how social verbs in the fairy tale of "as-Sultan al-Mashur" of Muhammad Atiyyatul Ibrasyi in Max Weber's theory. The researcher used this qualitative research using the descriptive approach, which is the search that obtains written metadata. The main source is the fairy tale " as-Sultan al-Mashur" taken from the international network. The data sources were taken from books that are looking for social verbs, books that are looking for social science for Max Weber, and books on the subject. The method of analysis of the data, including: data collection, data reduction, data presentation and data results. As to the results of the research, the researcher found two consequences of the Max Weber's theory, which consisted of social acts: 1) the traditional act signifies the custom of the sultan in his days. (2) The emotional act denotes an act of passion such as anger, vengeance, and suspicions. (3) A rational, value-based act signifies the etiquette of respect and pride. (4) The mental rationality is indicative of the objectives of doing things. الكلمات الرئيسية: الأفعال الاجتماعية، حكاية خرافية.